Cross-cultural adaptation and psychometric validation of the breast cancer stigma assessment scale among Chinese patients - Lin, Youbei; Li, Chuang; Li, Hongyu; Wang, Xiuli (Frontiers in Psychology, 2025)
BackgroundBreast cancer stigma significantly impacts patients’ psychological wellbeing, yet culturally validated assessment tools remain limited in Chinese contexts. This study aimed to translate and culturally adapt the Breast Cancer Stigma Assessment Scale (BCSAS) and evaluate its psychometric properties among Chinese breast cancer patients.MethodsFollowing Brislin’s translation model, the BCSAS was rigorously adapted through forward-backward translation and cultural adaptation. Six multidisciplinary experts (nursing psychology, n = 4; breast surgery, n = 2) evaluated content, semantic, and conceptual equivalence. A total of 550 questionnaires were distributed to women with breast cancer from three tertiary hospitals in western Liaoning, China, yielding 500 valid responses (response rate = 90.91%). Psychometric evaluation included content validity assessment, confirmatory factor analysis (CFA), reliability testing, and convergent validity assessment. Exploratory network analysis complemented CFA findings.ResultsThe Chinese version (C-BCSAS) demonstrated excellent content validity (S-CVI = 0.98), strong internal consistency (Cronbach’s α = 0.890; dimension-specific α = 0.712–0.876), and good test–retest reliability (ICC = 0.825, 95% CI = 0.691–0.903). CFA revealed fit indices of χ2/df = 4.446, CFI = 0.829, TLI = 0.800, RMSEA = 0.083. While slightly below commonly cited thresholds, all factor loadings substantially exceeded 0.50 (range: 0.540–0.846, p < 0.001), supporting item-level validity. The original seven-factor, 28-item structure was retained to preserve theoretical integrity and enable cross-cultural comparisons.ConclusionThe C-BCSAS is a reliable and culturally valid instrument for assessing breast cancer stigma in Chinese contexts, suitable for both clinical assessment and international comparative research.